Socio-economic determinants of subjective wellbeing toward Sustainable Development Goals: An insight from a developing country - Salameh, Anas A.; Amin, Sajid; Danish, Muhammad Hassan; Asghar, Nabila; Naveed, Rana Tahir; Munir, Mubbasher (Frontiers in Psychology, 2022)
One of the goals of happiness research is to identify the key factors that influence it. Therefore, the present research is designed to examine the determining factors of subjective wellbeing (SWB) in Pakistan. The present research is conducted by collecting the data of 1,566 households in Punjab, Pakistan, using the ordered logit and tobit model. The findings of this research confirm that income, education, government effectiveness, no perceived corruption, and perceived institutional quality improve wellbeing, while lower trust in family and friends, poor health status, living on rent, and dissatisfaction with the services of hospitals lower the level of wellbeing. But individuals with more social ties, who face barriers in health services, live more happily satisfied with their lives. Crime victimization and worrisome terrorism also lower the level of SWB. Findings of research strongly emphasize policymakers and government institutions to improve their quality and take essential measures for improving the governance structure.